Failure to Thrive and its Risk Factors in 0-24 Months Children in Bojnurd City of Iran during 2008-2013 - Hossein Lashkardoost; Saeid Doaei; Zohreh Akbari; Fatemeh Mashkooti; Ebrahim Hosseinzadeh; Andishe Hamedi (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: Failure to thrive (FTT) is a global problem and one of the most common health problems in childhood that involves many other social, economic, and cultural factors. Considering the adverse effects of FTT in the future of children, we studied FTT and its related factor in children under the age of 2 years in Bojnurd (the capital city of North Khorasan province, Iran). Methods: This study was a Retrospective cohort study on 1000 health records, born in 2008-2013. Stratified sampling method was applied and the data were collected using a checklist in the health centers. Finally, data were analyzed using Chi-square, Multiple logistic regression, and independent t-test in SPSS19 software. Significant level was set at 5%. Results: Incidence of FTT was calculated as 443 children (44.3%) in the children's first two years of life. A significant relationship was observed between FTT in children and head circumference disorders at birth (p=0.001), maternal age at delivery (p=0.01), mother's education level (OR=0.4   CI95% [0.2-0.8]  p=0.012), type of delivery (OR=0.5 CI95% [0.4-0.7]   p<0.001), unspecified gestational age (OR=3.6   CI95% [1.3-10.08   p=0.015]), and pregnancy under the age of 18 (OR=2.4   CI95% [1.1-5.3]  p=0.02).  Conclusion: Considering the high incidence of FTT in children, increasing awareness about timely feeding, promoting households' health, preventing and controlling infectious diseases should be improved.